PEMT Variants are Associated with Nonsyndromic Cleft Lip with or without Cleft Palate in Chile - Suazo, José; Salamanca, Carlos; González-Hormazábal, Patricio; Cáceres-Rojas, Gabriela; Pantoja, Roberto; Leiva, Noemi; Pardo, Rosa (Epigenomics, 2022)
To assess the association between variants and nonsyndromic cleft lip with or without cleft palate in Chile and the effects of these variants on global DNA methylation. The authors obtained genotypes for nine variants from 247 cases and 453 controls for genotype-phenotype associations. The effect of significant polymorphisms on global DNA methylation (percentage of long interspersed element-1 methylation) was evaluated in a subsample of 95 controls. After multiple comparison corrections, variants and were associated with nonsyndromic cleft lip with or without cleft palate. Carriers of risk alleles presented lower DNA methylation levels than noncarriers. According to functional analysis for risk variants from previous reports, the authors infer that a decrease of methyl group availability is occurring in affected subjects.